The era of dynamic audit with KPMG Clara: experience at Rahman Rahman Huq chartered accountants, KPMG - Ornob, Tamjid Shahriar (Brac University, 2024)
This internship report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Business Administration, 2023.